Impact of localized fine tuning in the performance of segmentation and classification of lung nodules from computed tomography scans using deep learning - Cai, Jingwei; Guo, Lin; Zhu, Litong; Xia, Li; Qian, Lingjun; Lure, Yuan-Ming Fleming; Yin, Xiaoping (Frontiers in Oncology, 2023)
Background: Algorithm malfunction may occur when there is a mismatch between the dataset with which it was developed and the dataset on which it was deployed. Methods: A baseline segmentation algorithm and a baseline classification algorithm were developed using public dataset of Lung Image Database Consortium to detect benign and malignant nodules, and two additional external datasets (i.e., HB and XZ) including 542 cases and 486 cases were involved for the independent validation of these two algorithms. To explore the impact of localized fine tuning on the individual segmentation and classification process, the baseline algorithms were fine tunned with CT scans of HB and XZ datasets, respectively, and the performance of the fine tunned algorithms was tested to compare with the baseline algorithms. Results: The proposed baseline algorithms of both segmentation and classification experienced a drop when directly deployed in external HB and XZ datasets. Comparing with the baseline validation results in nodule segmentation, the fine tunned segmentation algorithm obtained better performance in Dice coefficient, Intersection over Union, and Average Surface Distance in HB dataset (0.593 vs. 0.444; 0.450 vs. 0.348; 0.283 vs. 0.304) and XZ dataset (0.601 vs. 0.486; 0.482 vs. 0.378; 0.225 vs. 0.358). Similarly, comparing with the baseline validation results in benign and malignant nodule classification, the fine tunned classification algorithm had improved area under the receiver operating characteristic curve value, accuracy, and F1 score in HB dataset (0.851 vs. 0.812; 0.813 vs. 0.769; 0.852 vs. 0.822) and XZ dataset (0.724 vs. 0.668; 0.696 vs. 0.617; 0.737 vs. 0.668). Conclusions: The external validation performance of localized fine tunned algorithms outperformed the baseline algorithms in both segmentation process and classification process, which showed that localized fine tuning may be an effective way to enable a baseline algorithm generalize to site-specific use.